“Evil Father Earth” : Personification and Villainization of the Setting in N. K. Jemisin’s The Broken Earth - Niemi, Antti (My University, 2022)
Ecologically orientated writing and ecocritically motivated readings are increasingly common in the contemporary context of climate change. This increased eco-awareness is an acknowledgement of how the human relationship with nature is undergoing profound changes, which demand interdisciplinary investigation in both natural sciences and cultural studies. In literary analysis, science fiction writing offers windows into worlds that force us to critically re-examine our attitudes and practices concerning nature and non-human agency. In this thesis, I examine N. K. Jemisin’s The Broken Earth trilogy and its sentient setting, Father Earth. The dynamic planet of the trilogy is an example of heightened ecocentric personification and planetary-scale anthropomorphism, essentially a character itself. Through an analysis of Father Earth, I explore more generally how milieus and objects in literature can be seen as actors and characters within the narrative. This re-evaluation of object agency is done using concepts of ecocriticism, eco-philosophy, anthropology, and narratology. The unstable ecological state of the Stillness also compares to James Lovelock’s Gaia theory in that the planet has become active and unwell due to the destabilization of its equilibrium. Ultimately, I suggest that the way Jemisin personifies the setting of The Broken Earth as a mistreated and vengeful character alludes to the central theme of her work. Nature should not be taken for granted and exploited without consequence, as it is more or less directly linked to human wellbeing in the end. By harvesting the magic lifeforce of the Earth, the ancient inhabitants of the Stillness became corrupted and drove the ecosystem to an unstable state. This acts as an allusion to the unsustainable economic practices of the 20th and 21st century that have been a target of critique for ecocritics and environmentalists for decades now. Using clever second person narration, Jemisin addresses the reader more directly, encouraging further evaluation of our individual actions and anticipation of their long-term effects, comparable to the choices that Essun faces in The Broken Earth.
Keywords: ecocriticism, personification, object agency, Gaia, genius loci, hyperobjects